2020
DOI: 10.1111/tpj.15013
|View full text |Cite
|
Sign up to set email alerts
|

OsSYL2AA, an allele identified by gene‐based association, increases style length in rice (Oryza sativa L.)

Abstract: Stigma characteristics are important factors affecting the seed yield of hybrid rice per unit area. Natural variation of stigma characteristics has been reported in rice, but the genetic basis for this variation is largely unknown. We performed a genome-wide association study on three stigma characteristics in six environments using 1.3 million single-nucleotide polymorphism (SNPs) characterized in 353 diverse accessions of Oryza sativa. An abundance of phenotypic variation was present in the three stigma char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…We investigated the stigma characteristics of these three accessions. W1944 had longer stigmas than HY and CR6078, which is consistent with the finding that eight accessions of O. rufipogon and four of O. nivara had CC alleles at OsSYL2 and OsSYL3 , contributing to an increase in the stigma length in these wild Oryza species ( Dang et al, 2020 ). Histological analysis of thin sections from these CR6078 embryos showed a cleavage between the coleoptile and epidermis without any tissue covering the coleoptile ( Figure 1E ).…”
Section: Resultssupporting
confidence: 88%
“…We investigated the stigma characteristics of these three accessions. W1944 had longer stigmas than HY and CR6078, which is consistent with the finding that eight accessions of O. rufipogon and four of O. nivara had CC alleles at OsSYL2 and OsSYL3 , contributing to an increase in the stigma length in these wild Oryza species ( Dang et al, 2020 ). Histological analysis of thin sections from these CR6078 embryos showed a cleavage between the coleoptile and epidermis without any tissue covering the coleoptile ( Figure 1E ).…”
Section: Resultssupporting
confidence: 88%
“…In rice, the stigma characteristics, a complex quantitative trait, are controlled by multiple genes with minor phenotypic effects (Uga et al 2003 , 2010 ; Yu et al 2003 ). To the best of our knowledge, 37 quantitative trait loci (QTLs) have been detected for the STL and they are distributed on all the 12 chromosomes (Uga et al 2003 , 2010 ; Yan et al 2009 ; Li et al 2010 ; Marathi et al 2015 ; Dang et al 2016 , 2020 ). Uga et al ( 2003 ) reported that the QTL qSTL-4 on the chromosome 4 has the largest additive effect, and the allele from accession W1944 can increase the STL by 0.106 mm compared with Pei-kul.…”
Section: Introductionmentioning
confidence: 99%
“…Uga et al ( 2003 ) reported that the QTL qSTL-4 on the chromosome 4 has the largest additive effect, and the allele from accession W1944 can increase the STL by 0.106 mm compared with Pei-kul. Thirty-nine QTLs have been identified for the SYL and they are located on chromosomes 1, 2, 3, 4, 6, 7, 9, 10, and 11 (Uga et al 2003 , 2010 ; Li et al 2010 ; Marathi et al 2015 ; Dang et al 2016 , 2020 ; Zhou et al 2017 ). Uga et al ( 2010 ) also reported that the QTL qSYL-3 on the chromosome 3 has the largest additive effect, and the allele from IR64 can increase the SYL by 0.102 mm compared with Kinandang Patong.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations